2022
DOI: 10.3389/fpubh.2022.993801
|View full text |Cite
|
Sign up to set email alerts
|

Review of the impact of urban parks and green spaces on residence prices in the environmental health context

Abstract: Urban parks have consistently played an important role in people's living environment, reflecting house prices and the extent of the people's attention. Although many studies have been conducted in this filed, the consolidated related research has not been discussed often. Therefore, related papers on the impact of urban park green spaces on housing prices in recent years should be sorted out. Different choices of urban parks and green areas will undoubtedly influence research methods, housing preferences and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…Green space also reduces heat and air pollution, impacting environmental health ( 73 ). Last but not least, the presence of green space improves real estate values ( 74 ) and provides opportunities for jobs and small businesses ( 72 ). All these outcomes interact to contribute to individual and community QoL, but research is warranted to examine these different pathways in a synergistic and systems framework.…”
Section: Discussionmentioning
confidence: 99%
“…Green space also reduces heat and air pollution, impacting environmental health ( 73 ). Last but not least, the presence of green space improves real estate values ( 74 ) and provides opportunities for jobs and small businesses ( 72 ). All these outcomes interact to contribute to individual and community QoL, but research is warranted to examine these different pathways in a synergistic and systems framework.…”
Section: Discussionmentioning
confidence: 99%
“…Neckel [19] and Silva [20] quantitatively assessed the economic value of urban parks in Brazil and Portugal using CVM, WTD (willingness to donate), and questionnaire methods. Kim [21] and Chen [22] assessed the value of parks through changes in residential prices and concluded that urban parks, especially green spaces, have a positive impact on residential prices.…”
Section: Benefits and Value Analysis Of Urban-parkland Usementioning
confidence: 99%
“…Mental health concerns among younger generations in developed countries continue to increase (Botha, 2023) and it is largely agreed that social ties play a beneficial role in the maintenance of psychological well-being (Kawachi, 2001). Thus, access to green spaces in urban and suburban environments is becoming increasingly important to new home buyers (Chen, 2022).…”
Section: Introductionmentioning
confidence: 99%